2013
DOI: 10.1097/jnr.0b013e3182921fc9
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Geriatric Depression and Health-Promoting Behaviors Among Community-Dwelling Seniors

Abstract: Participants practiced less than the recommended level of health-promoting behaviors. We found a negative correlation between the geriatric depression score and health-promoting behavior. Results can be referenced to develop strategies to promote healthy aging in the community, especially with regard to promoting greater social participation and increased activity for community-dwelling older adults experiencing depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…A previous study [38] showed 15.3% depressive neurosis and 5.9% major depression in the older adult community; however, other studies have found the prevalence of geriatric depression to be approximately 20.0% [39]. A comparison of these studies is difficult because of differences in research methodology, study population, diagnostic criteria, and instruments used [38].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study [38] showed 15.3% depressive neurosis and 5.9% major depression in the older adult community; however, other studies have found the prevalence of geriatric depression to be approximately 20.0% [39]. A comparison of these studies is difficult because of differences in research methodology, study population, diagnostic criteria, and instruments used [38].…”
Section: Discussionmentioning
confidence: 99%
“…Higher health-promoting behaviors showed lower levels of depression, which was consistent with other study findings. 13,26) A negative correlation between the geriatric depression score and health-promoting behavior was found. The Geriatric Depression Scale score was negatively associated with health-promoting behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, an increasing number of China’s retirees, especially women, have organized themselves into morning exercise groups and dance groups, which can be easily spotted in China’s city parks or street corners. However, there have not been enough vigorous evaluation studies in China on the health benefits of regular physical activity among the older adults (Chang et al, 2013). China has an opportunity to contribute to this important body of knowledge.…”
Section: To Establish An Aging Friendly Societymentioning
confidence: 99%